Oxidized crosslinked asphalt coated resin hard carbon negative electrode material and preparation method thereof

Through the preparation method of oxidized crosslinked asphalt-coated resin hard carbon negative electrode material, the problem of unstable storage of graphite materials in sodium ion batteries is solved, and the capacity and efficiency of the battery are significantly improved.

CN119581533AInactive Publication Date: 2025-03-07GUANGDONG KAIJIN NEW ENERGY TECH CORP LTD

Patent Information

Application Number
CN202411779916.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing sodium ion battery negative electrode material graphite is too small to intercalate/detach the sodium ions and lacks stable Na-C binary compounds, resulting in unstable storage of sodium ions.

Method used

The resin hard carbon negative electrode material is coated with oxidized crosslinked asphalt. The preparation method includes resin pretreatment, mechanical crushing, low-temperature pre-charging, activated pore formation, asphalt coating and low-temperature oxidation crosslinking, and other steps. Through these steps, the resin hard carbon is uniformly coated and formed a more stable carbon structure.

Benefits of technology

The specific surface area of ​​the material is significantly reduced, the first reversible capacity of the battery and the initial Coulomb efficiency are improved, and the diffusion and adsorption capacity of sodium ions are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005172536170000141
    Figure BDA0005172536170000141
Patent Text Reader

Abstract

The invention discloses an oxidized crosslinked asphalt coated resin hard carbon negative electrode material and a preparation method thereof. The preparation method comprises the following steps: S1, pre-treating resin to obtain a resin precursor; s2, performing mechanical pulverization, low-temperature pre-carbonization and airflow pulverization treatment on the resin precursor to obtain low-temperature pre-carbonized ground powder; s3, the low-temperature pre-carbonized ground powder is subjected to activation pore forming and high-temperature carbonization treatment, and resin hard carbon is obtained; s4, uniformly mixing the resin hard carbon and the asphalt to obtain a mixture; s5, performing asphalt melting coating and low-temperature oxidation cross-linking treatment on the mixture to obtain oxidation cross-linked asphalt coated resin hard carbon; s6, performing high-temperature carbonization treatment on the oxidized cross-linked asphalt coated resin hard carbon to obtain coated hard carbon; and S7, carrying out post-treatment on the coated hard carbon to obtain the oxidized crosslinked asphalt coated resin hard carbon negative electrode material. The oxidized cross-linked asphalt coated resin hard carbon negative electrode material has a relatively low specific surface area, and the first reversible capacity and the initial coulombic efficiency of a battery can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrode materials, and in particular relates to an oxidatively cross-linked asphalt-coated resin hard carbon negative electrode material and a preparation method thereof. Background Art

[0002] With the continuous growth of global energy demand and the improvement of environmental protection awareness, the development of efficient and sustainable energy storage systems has become a top priority. Lithium-ion batteries are widely used in fields such as portable electronic devices and electric vehicles due to their high energy density and long cycle life. However, the limited earth reserves, uneven distribution and high price of lithium resources have restricted the large-scale application of lithium-ion batteries. In contrast, sodium resources are abundant, cheap and have similar chemical properties to lithium. Therefore, sodium-ion batteries are regarded as a potential alternative to lithium-ion batteries and have received extensive attention and research. Although sodium-ion batteries have many theoretical advantages, they still face some challenges in practical applications. Graphite, a common negative electrode material for lithium-ion batteries, has a small interlayer spacing, so sodium ions cannot be inserted / extracted between its carbon layers, and there is a lack of stable Na-C binary compounds. The Na-C bond energy is extremely weak and cannot stably store sodium ions. Therefore, graphite is not suitable as a negative electrode material for sodium-ion batteries.

[0003] In order to overcome the above problems, researchers have developed a variety of negative electrode materials for sodium ion batteries, including alloys, metal compounds and carbon-based materials. Among these negative electrode materials, hard carbon is often used as a negative electrode material for sodium batteries because of its abundant sources, strong intermolecular forces between resin molecules, highly adjustable and relatively stable structure, strong carbon-forming ability and high carbon yield after pyrolysis. Among them, micropores and defects (such as oxygen-containing groups) as active sites for sodium ion storage are crucial to the capacity improvement of hard carbon materials, and the introduction of oxygen-containing functional groups and the adjustment of pore structure can be achieved through oxidation processes. However, some oxidation processes will inevitably significantly increase the specific surface area, resulting in a decrease in the initial Coulombic efficiency.

[0004] Therefore, there is an urgent need for an oxidatively cross-linked asphalt-coated resin hard carbon negative electrode material and a preparation method thereof to solve the deficiencies of the existing technical problems. Summary of the invention

[0005] In view of the above problems, the purpose of the present invention is to provide an oxidized cross-linked asphalt coated resin hard carbon negative electrode material and a preparation method thereof. The oxidized cross-linked asphalt coated resin hard carbon negative electrode material has a low specific surface area and can significantly improve the first reversible capacity and initial coulombic efficiency of the battery.

[0006] To achieve the above objectives, the first aspect of the present invention provides a method for preparing an oxidatively cross-linked asphalt-coated resin hard carbon negative electrode material, the steps comprising:

[0007] S1, pre-treating the resin to obtain a resin precursor;

[0008] S2, sequentially subjecting the resin precursor to mechanical pulverization, low-temperature pre-carbonization under a first inert atmosphere, and airflow pulverization to obtain a low-temperature pre-carbonized abrasive material;

[0009] S3, subjecting the low-temperature pre-carbonized ground powder to activation pore-forming treatment and first high-temperature carbonization treatment in sequence to obtain resin hard carbon;

[0010] S4, mixing the resin hard carbon and asphalt evenly to obtain a mixture, wherein the mass ratio of the resin hard carbon to the asphalt is 100:1-5;

[0011] S5, melting and coating the mixture with asphalt in a protective atmosphere, and then switching the protective atmosphere to air atmosphere for low-temperature oxidation cross-linking treatment to obtain oxidative cross-linked asphalt-coated resin hard carbon;

[0012] S6, subjecting the oxidatively cross-linked asphalt-coated resin hard carbon to a second high-temperature carbonization treatment in a second inert atmosphere to obtain coated hard carbon;

[0013] S7, post-treating the coated hard carbon to obtain coated hard carbon powder.

[0014] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0015] (1) The high viscosity of asphalt after melting is not conducive to the coating of the hard carbon surface, and uneven coating is prone to occur. Based on this, in step S2 of the present invention, the resin precursor is converted into a low-temperature pre-carbonized abrasive material with a small particle size and uniform distribution through mechanical crushing, low-temperature pre-carbonization under a first inert atmosphere, and airflow crushing treatment. The low-temperature pre-carbonized abrasive material has a larger specific surface area and better fluidity, and can significantly improve the contact area and dispersion uniformity when mixed with asphalt, thereby ensuring that the asphalt can be more evenly coated on the surface of each resin hard carbon particle; at the same time, the activation pore-forming treatment in S3 will introduce a Some active sites or functional groups are added to the surface of the material, which help to improve the reactivity of the material, thereby promoting the uniform coating of asphalt on the surface of the resin hard carbon; and the carbon structure formed during the first high-temperature carbonization treatment in S3 is more stable and strong, which enhances the overall mechanical strength of the resin hard carbon, making it less likely to break when mixed with asphalt. Therefore, steps S2 and S3 of the present application create favorable conditions for the uniform coating of asphalt and resin hard carbon in subsequent steps by refining particles, enhancing surface activity and improving mechanical strength.

[0016] (2) In step S5 of the present invention, the asphalt is attached to the surface of the resin hard carbon in the form of irregular particles, and at the same time, some carbon atoms on the asphalt molecular chain react with oxygen to form oxygen-containing functional groups (such as aromatic ethers, aromatic aldehydes / ketones or esters). Subsequently, in the second high-temperature carbonization process in S6, the oxygen-containing functional groups in the oxidized asphalt begin to decompose and release a large number of free radicals. These free radicals participate in further cross-linking reactions, promoting the reorganization of the internal structure of the material. As the temperature rises, the original ordered carbon layer is gradually peeled off, and the newly formed carbon structure is more disordered and the crystallite size is smaller, which makes the coated hard carbon have higher mechanical strength, more closed pores and ultra-micropores, reduces the specific surface area of ​​the resin hard carbon, improves the surface wettability of the resin hard carbon and the electrolyte, is beneficial to the diffusion and adsorption of sodium ions, and significantly improves the first reversible capacity and initial coulomb efficiency of the battery.

[0017] As an embodiment, the pretreatment in step S1 includes: mixing the resin and the solvent, then performing homogenization and heating and curing in sequence. Specifically, the heating and curing is performed in an oven.

[0018] As one embodiment, the temperature of heating and curing in step S1 is 60℃~200℃, and the time is 5h~50h; specifically, the temperature of heating and curing may be but not limited to 60℃, 70℃, 80℃, 90℃, 100℃, 110℃, 150℃, 170℃, 190℃, 200℃; the time may be but not limited to 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 20h, 22h, 27h, 32h, 38h, 40h, 42h, 44h, 46h, 50h.

[0019] As an embodiment, the resin is at least one of phenolic resin, epoxy resin and furfural resin; the solvent is at least one of water, alcohol and ketone.

[0020] As an implementation scheme, after the mechanical crushing in step S2, a 12 mm sieve is used for screening.

[0021] As an implementation scheme, the temperature of low-temperature pre-carbonization in step S2 is 350°C to 700°C, and the time is 0.5h to 10h. Specifically, the temperature of low-temperature pre-carbonization may be, but not limited to, 350°C, 420°C, 450°C, 500°C, 300°C, 330°C, 380°C, 420°C, 480°C, 540°C, 580°C, 620°C, 650°C, 680°C, 700°C; the time may be, but not limited to, 0.5h, 3h, 4h, 5h, 6h, 7h, 8h, 10h.

[0022] As an embodiment, the first inert atmosphere in step S2 is at least one of argon and nitrogen.

[0023] As an embodiment, the particle size Dv50 of the low temperature pre-carbonized ground powder in step S2 is 4 μm to 10 μm.

[0024] As an embodiment, the atmosphere of the activation pore-forming treatment in step S3 is a mixed gas composed of at least two of water vapor, carbon dioxide, and nitrogen. The temperature of the activation pore-forming treatment is 700°C to 1000°C, and the time is 1h to 10h; for example, the temperature of the activation pore-forming treatment may be, but is not limited to, 700°C, 800°C, 900°C, 1000°C, and the time is 1h, 2h, 3h, 4h, 5h, 6h, 8h, 10h.

[0025] As an embodiment, the temperature of the first high temperature carbonization treatment in step S3 is 1100°C to 1600°C, and the time is 0.5 to 8 hours. Specifically, the temperature of the first high temperature carbonization treatment may be, but not limited to, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, and the time may be, but not limited to, 0.5h, 3h, 4h, 5h, 6h, 7h, 8h.

[0026] As an embodiment, the asphalt in step S4 is selected from at least one of coal asphalt, petroleum asphalt, modified asphalt and mesophase asphalt, and the softening point of the asphalt is 100-280°C.

[0027] As one implementation scheme, the asphalt melt coating in step S5 includes: heating to 200-400°C at a heating rate of 1-10°C / min under a protective atmosphere, and keeping warm for 0.5-5h; the low-temperature oxidation cross-linking treatment includes: keeping warm at 200-400°C for 0.5-5h; specifically, the heating rate may be but not limited to 1°C / min, 2°C / min, 3°C / min, 4°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min; specifically, the temperature of the asphalt melt coating and low-temperature oxidation cross-linking treatment may be but not limited to 200°C, 250°C, 270°C, 290°C, 320°C, 350°C, 380°C, 400°C, more specifically, the insulation time may be but not limited to 0.5h, 1h, 3h, 4h, 5h.

[0028] As an implementation scheme, the low-temperature oxidation cross-linking treatment in step S5 is carried out in a box furnace, a CVD furnace, a rotary kiln, a pusher kiln, a roller kiln or a tunnel kiln.

[0029] As an embodiment, the protective atmosphere in step S5 is at least one of argon and nitrogen. Specifically, the air atmosphere can be air or oxygen.

[0030] As an embodiment, the second inert atmosphere in step S6 is at least one of argon and nitrogen, the temperature of the second high temperature carbonization treatment is 1100°C to 1600°C, and the time is 0.5h to 8h. Specifically, the temperature of the second high temperature carbonization treatment may be, but not limited to, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, 1500°C, 1600°C; the time may be, but not limited to, 0.5h, 2h, 3h, 4h, 5h, 6h, 7h, 8h.

[0031] As an embodiment, the post-treatment in step S7 includes depolymerization, screening, and demagnetization treatment in sequence.

[0032] As an implementation scheme, the screening in step S7 is performed using a 325-mesh screen.

[0033] Correspondingly, the second aspect of the present invention also provides an oxidized cross-linked asphalt-coated resin hard carbon negative electrode material, which is prepared by the above-mentioned method for preparing the oxidized cross-linked asphalt-coated resin hard carbon negative electrode material. DETAILED DESCRIPTION

[0034] In order to better illustrate the purpose, technical solution and beneficial effects of the present invention, the present invention will be further described below in conjunction with examples and comparative examples. It should be noted that the scope of the present invention is not limited to the scope described in the examples.

[0035] Example 1

[0036] This embodiment provides a method for preparing an oxidatively cross-linked asphalt-coated resin hard carbon negative electrode material, the steps comprising:

[0037] S1, 20kg of phenolic resin and 10kg of anhydrous ethanol were mixed, stirred at room temperature for 1h, and then heated and cured in an oven at 95°C for 10h to obtain a resin precursor;

[0038] S2, the resin precursor is mechanically crushed and passed through a 12 mm mesh sieve, then placed in a heating furnace and kept at 400°C for 6 hours, cooled to room temperature, taken out and subjected to air flow crushing, and then sieved through a 325 mesh sieve to obtain a low-temperature pre-carbonized ground powder with a particle size Dv50 of 5 μm; wherein the atmosphere in the heating furnace is nitrogen, and the nitrogen flow rate is 1 L / min;

[0039] S3, placing the low-temperature pre-carbonized ground powder in a CVD furnace and activating and pore-forming treatment at 800°C for 2 hours, then placing it in a box furnace and high-temperature carbonizing at 1300°C for 4 hours and then cooling it to room temperature to obtain resin hard carbon; wherein the atmosphere in the CVD furnace is a mixed gas composed of nitrogen and carbon dioxide, the nitrogen flow rate is 1L / min, and the carbon dioxide flow rate is 2L / min; the atmosphere in the box furnace is nitrogen, and the nitrogen flow rate is 1L / min;

[0040] S4, mixing resin hard carbon and petroleum asphalt in a mass ratio of 100:1 to obtain a mixture, wherein the softening point of the petroleum asphalt is 150° C. and the particle size Dv50 of the petroleum asphalt is 10 μm;

[0041] S5. Place the mixture in a CVD furnace, heat it to 250°C at a heating rate of 8°C / min under a nitrogen atmosphere, keep it warm for 1 hour, then switch the nitrogen to compressed air, and continue to keep it warm for 2 hours to obtain oxidative cross-linked asphalt-coated resin hard carbon; wherein the nitrogen flow rate is 1L / min, and the compressed air flow rate is 2L / min;

[0042] S6, placing the crucible containing the oxidized cross-linked asphalt coated resin hard carbon in a heating furnace and carbonizing it at 1150° C. for 4 hours, cooling it to room temperature and taking it out to obtain coated hard carbon; wherein the atmosphere in the heating furnace is nitrogen, and the nitrogen flow rate is 1 L / min;

[0043] S7. The coated hard carbon is sequentially broken up and depolymerized, sieved with a 325-mesh sieve, and demagnetized to obtain an oxidized cross-linked asphalt-coated resin hard carbon negative electrode material.

[0044] Example 2

[0045] This embodiment provides a method for preparing an oxidatively cross-linked asphalt-coated resin hard carbon negative electrode material, the steps comprising:

[0046] S1, 20kg of phenolic resin and 10kg of anhydrous ethanol were mixed, stirred at room temperature for 1h, and then heated and cured in an oven at 105°C for 12h to obtain a resin precursor;

[0047] S2, the resin precursor is mechanically crushed and passed through a 12 mm mesh sieve, then placed in a heating furnace and kept at 500°C for 5.5 hours, cooled to room temperature, taken out and subjected to air flow crushing, and then sieved through a 325 mesh sieve to obtain a low-temperature pre-carbonized ground powder with a particle size Dv50 of 5 μm; wherein the atmosphere in the heating furnace is nitrogen, and the nitrogen flow rate is 1 L / min;

[0048] S3, placing the low-temperature pre-carbonized ground powder in a CVD furnace and activating and pore-forming treatment at 1000°C for 3 hours, then placing it in a box furnace and high-temperature carbonizing at 1100°C for 6 hours and then cooling it to room temperature to obtain resin hard carbon; wherein the atmosphere in the CVD furnace is a mixed gas composed of nitrogen and carbon dioxide, the nitrogen flow rate is 1L / min, and the carbon dioxide flow rate is 2L / min; the atmosphere in the box furnace is nitrogen, and the nitrogen flow rate is 1L / min;

[0049] S4, mixing resin hard carbon and petroleum asphalt in a mass ratio of 100:2.5 to obtain a mixture, wherein the softening point of the petroleum asphalt is 180° C. and the particle size Dv50 of the petroleum asphalt is 10 μm;

[0050] S5. Place the mixture in a CVD furnace, heat it to 300°C at a heating rate of 5°C / min under a nitrogen atmosphere, keep it warm for 1.5 hours, then switch the nitrogen to compressed air, and continue to keep it warm for 3 hours to obtain oxidative cross-linked asphalt-coated resin hard carbon; the nitrogen flow rate is 1L / min, and the compressed air flow rate is 3L / min;

[0051] S6, placing the crucible containing the oxidized cross-linked asphalt coated resin hard carbon in a heating furnace and carbonizing it at 1200° C. for 4 hours, cooling it to room temperature and taking it out to obtain coated hard carbon; wherein the atmosphere in the heating furnace is nitrogen, and the nitrogen flow rate is 1 L / min;

[0052] S7. The coated hard carbon is sequentially broken up and depolymerized, sieved with a 325-mesh sieve, and demagnetized to obtain an oxidized cross-linked asphalt-coated resin hard carbon negative electrode material.

[0053] Example 3

[0054] This embodiment provides a method for preparing an oxidatively cross-linked asphalt-coated resin hard carbon negative electrode material, the steps comprising:

[0055] S1, 20kg of phenolic resin and 10kg of anhydrous ethanol were mixed, stirred at room temperature for 1h, and then heated and cured in an oven at 85°C for 18h to obtain a resin precursor;

[0056] S2, the resin precursor is mechanically crushed and passed through a 12 mm mesh sieve, then placed in a heating furnace and kept at 600°C for 4 hours, cooled to room temperature, taken out and subjected to air flow crushing, and then sieved through a 325 mesh sieve to obtain a low-temperature pre-carbonized ground powder with a particle size Dv50 of 5 μm; wherein the atmosphere in the heating furnace is nitrogen, and the nitrogen flow rate is 1 L / min;

[0057] S3, placing the low-temperature pre-carbonized ground powder in a CVD furnace and activating and pore-forming treatment at 650°C for 6 hours, then placing it in a box furnace and high-temperature carbonizing at 1500°C for 3.5 hours and then cooling it to room temperature to obtain resin hard carbon; wherein the atmosphere in the CVD furnace is a mixed gas composed of nitrogen and carbon dioxide, the nitrogen flow rate is 1L / min, and the carbon dioxide flow rate is 2L / min; the atmosphere in the box furnace is nitrogen, and the nitrogen flow rate is 1L / min;

[0058] S4, mixing resin hard carbon and petroleum asphalt in a mass ratio of 100:5 to obtain a mixture, wherein the softening point of the petroleum asphalt is 210° C. and the particle size Dv50 of the petroleum asphalt is 10 μm;

[0059] S5. Place the mixture in a CVD furnace, heat it to 350°C at a heating rate of 4°C / min under a nitrogen atmosphere, keep it warm for 2 hours, then switch the nitrogen to compressed air, and continue to keep it warm for 4 hours to obtain oxidative cross-linked asphalt-coated resin hard carbon; the nitrogen flow rate is 1L / min, and the compressed air flow rate is 4L / min;

[0060] S6, placing the crucible containing the oxidized cross-linked asphalt coated resin hard carbon in a heating furnace and carbonizing it at 1250° C. for 4 hours, cooling it to room temperature and taking it out to obtain coated hard carbon; wherein the atmosphere in the heating furnace is nitrogen, and the nitrogen flow rate is 1 L / min;

[0061] S7. The coated hard carbon is sequentially broken up and depolymerized, sieved with a 325-mesh sieve, and demagnetized to obtain an oxidized cross-linked asphalt-coated resin hard carbon negative electrode material.

[0062] Example 4

[0063] This embodiment provides a method for preparing an oxidatively cross-linked asphalt-coated resin hard carbon negative electrode material, the steps comprising:

[0064] S1, 20kg of phenolic resin and 10kg of anhydrous ethanol were mixed, stirred at room temperature for 1h, and then heated and cured in an oven at 95°C for 10h to obtain a resin precursor;

[0065] S2, the resin precursor is mechanically crushed and passed through a 12 mm mesh sieve, then placed in a heating furnace and kept at 400°C for 6 hours, cooled to room temperature, taken out and subjected to air flow crushing, and then sieved through a 325 mesh sieve to obtain a low-temperature pre-carbonized ground powder with a particle size Dv50 of 5 μm; wherein the atmosphere in the heating furnace is nitrogen, and the nitrogen flow rate is 1 L / min;

[0066] S3, placing the low-temperature pre-carbonized ground powder in a CVD furnace and activating and pore-forming treatment at 800°C for 2 hours, then placing it in a box furnace and high-temperature carbonizing at 1300°C for 4 hours and then cooling it to room temperature to obtain resin hard carbon; wherein the atmosphere in the CVD furnace is a mixed gas composed of nitrogen and carbon dioxide, the nitrogen flow rate is 1L / min, and the carbon dioxide flow rate is 2L / min; the atmosphere in the box furnace is nitrogen, and the nitrogen flow rate is 1L / min;

[0067] S4, mixing resin hard carbon and petroleum asphalt in a mass ratio of 100:2 to obtain a mixture, wherein the softening point of the petroleum asphalt is 210° C. and the particle size Dv50 of the petroleum asphalt is 10 μm;

[0068] S5. Place the mixture in a CVD furnace, heat it to 300°C at a heating rate of 8°C / min under a nitrogen atmosphere, keep it warm for 1 hour, then switch the nitrogen to compressed air, and continue to keep it warm for 3 hours to obtain oxidative cross-linked asphalt-coated resin hard carbon; wherein the nitrogen flow rate is 1L / min and the compressed air flow rate is 2L / min;

[0069] S6, placing the crucible containing the oxidized cross-linked asphalt coated resin hard carbon in a heating furnace and carbonizing it at 1200° C. for 4 hours, cooling it to room temperature and taking it out to obtain coated hard carbon; wherein the atmosphere in the heating furnace is nitrogen, and the nitrogen flow rate is 1 L / min;

[0070] S7. The coated hard carbon is sequentially broken up and depolymerized, sieved with a 325-mesh sieve, and demagnetized to obtain an oxidized cross-linked asphalt-coated resin hard carbon negative electrode material.

[0071] Example 5

[0072] This embodiment provides a method for preparing an oxidatively cross-linked asphalt-coated resin hard carbon negative electrode material, the steps comprising:

[0073] S1, 20kg of phenolic resin and 10kg of anhydrous ethanol were mixed, stirred at room temperature for 1h, and then heated and cured in an oven at 95°C for 10h to obtain a resin precursor;

[0074] S2, the resin precursor is mechanically crushed and passed through a 12 mm mesh sieve, then placed in a heating furnace and kept at 400°C for 6 hours, cooled to room temperature, taken out and subjected to air flow crushing, and then sieved through a 325 mesh sieve to obtain a low-temperature pre-carbonized ground powder with a particle size Dv50 of 5 μm; wherein the atmosphere in the heating furnace is nitrogen, and the nitrogen flow rate is 1 L / min;

[0075] S3, placing the low-temperature pre-carbonized ground powder in a CVD furnace and activating and pore-forming treatment at 800°C for 2 hours, then placing it in a box furnace and high-temperature carbonizing at 1300°C for 4 hours and then cooling it to room temperature to obtain resin hard carbon; wherein the atmosphere in the CVD furnace is a mixed gas composed of nitrogen and carbon dioxide, the nitrogen flow rate is 1L / min, and the carbon dioxide flow rate is 2L / min; the atmosphere in the box furnace is nitrogen, and the nitrogen flow rate is 1L / min;

[0076] S4, mixing resin hard carbon and petroleum asphalt in a mass ratio of 100:2 to obtain a mixture, wherein the softening point of the petroleum asphalt is 210° C. and the particle size Dv50 of the petroleum asphalt is 10 μm;

[0077] S5. Place the mixture in a CVD furnace, heat it to 350°C at a heating rate of 8°C / min under a nitrogen atmosphere, keep it warm for 0.5h, then switch the nitrogen to compressed air, and continue to keep it warm for 3h to obtain oxidative cross-linked asphalt-coated resin hard carbon; wherein the nitrogen flow rate is 1L / min and the compressed air flow rate is 3L / min;

[0078] S6, placing the crucible containing the oxidized cross-linked asphalt coated resin hard carbon in a heating furnace and carbonizing it at 1250° C. for 4 hours, cooling it to room temperature and taking it out to obtain coated hard carbon; wherein the atmosphere in the heating furnace is nitrogen, and the nitrogen flow rate is 1 L / min;

[0079] S7. The coated hard carbon is sequentially broken up and depolymerized, sieved with a 325-mesh sieve, and demagnetized to obtain an oxidized cross-linked asphalt-coated resin hard carbon negative electrode material.

[0080] Comparative Example 1

[0081] This comparative example provides a method for preparing an oxidatively cross-linked asphalt-coated resin hard carbon negative electrode material, the steps comprising:

[0082] S1, 20kg of phenolic resin and 10kg of anhydrous ethanol were mixed, stirred at room temperature for 1h, and then heated and cured in an oven at 95°C for 10h to obtain a resin precursor;

[0083] S2, the resin precursor is mechanically crushed and passed through a 12 mm mesh sieve, then placed in a heating furnace and kept at 400°C for 6 hours, cooled to room temperature, taken out and subjected to air flow crushing, and then sieved through a 325 mesh sieve to obtain a low-temperature pre-carbonized ground powder with a particle size Dv50 of 5 μm; wherein the atmosphere in the heating furnace is nitrogen, and the nitrogen flow rate is 1 L / min;

[0084] S3, placing the low-temperature pre-carbonized ground powder in a CVD furnace and activating and pore-forming treatment at 800°C for 2 hours, then placing it in a box furnace and high-temperature carbonizing at 1300°C for 4 hours and then cooling it to room temperature to obtain resin hard carbon; wherein the atmosphere in the CVD furnace is a mixed gas composed of nitrogen and carbon dioxide, the nitrogen flow rate is 1L / min, and the carbon dioxide flow rate is 2L / min; the atmosphere in the box furnace is nitrogen, and the nitrogen flow rate is 1L / min;

[0085] S4, mixing resin hard carbon and petroleum asphalt in a mass ratio of 100:0.5 to obtain a mixture, wherein the softening point of the petroleum asphalt is 90° C. and the particle size Dv50 of the petroleum asphalt is 10 μm;

[0086] S5. Place the mixture in a CVD furnace, heat it to 200°C at a heating rate of 8°C / min under a nitrogen atmosphere, keep it warm for 1 hour, then switch the nitrogen to compressed air, and continue to keep it warm for 1 hour to obtain oxidative cross-linked asphalt-coated resin hard carbon; wherein the nitrogen flow rate is 1L / min, and the compressed air flow rate is 1L / min;

[0087] S6, placing the crucible containing the oxidized cross-linked asphalt coated resin hard carbon in a heating furnace and carbonizing it at 1100° C. for 4 hours, cooling it to room temperature and taking it out to obtain coated hard carbon; wherein the atmosphere in the heating furnace is nitrogen, and the nitrogen flow rate is 1 L / min;

[0088] S7. The coated hard carbon is sequentially broken up and depolymerized, sieved with a 325-mesh sieve, and demagnetized to obtain an oxidized cross-linked asphalt-coated resin hard carbon negative electrode material.

[0089] Comparative Example 2

[0090] This comparative example provides a method for preparing an oxidatively cross-linked asphalt-coated resin hard carbon negative electrode material, the steps comprising:

[0091] S1, 20kg of phenolic resin and 10kg of anhydrous ethanol were mixed, stirred at room temperature for 1h, and then heated and cured in an oven at 95°C for 10h to obtain a resin precursor;

[0092] S2, the resin precursor is mechanically crushed and passed through a 12 mm mesh sieve, then placed in a heating furnace and kept at 400°C for 6 hours, cooled to room temperature, taken out and subjected to air flow crushing, and then sieved through a 325 mesh sieve to obtain a low-temperature pre-carbonized ground powder with a particle size Dv50 of 5 μm; wherein the atmosphere in the heating furnace is nitrogen, and the nitrogen flow rate is 1 L / min;

[0093] S3, placing the low-temperature pre-carbonized ground powder in a CVD furnace and activating and pore-forming treatment at 800°C for 2 hours, then placing it in a box furnace and high-temperature carbonizing at 1300°C for 4 hours and then cooling it to room temperature to obtain resin hard carbon; wherein the atmosphere in the CVD furnace is a mixed gas composed of nitrogen and carbon dioxide, the nitrogen flow rate is 1L / min, and the carbon dioxide flow rate is 2L / min; the atmosphere in the box furnace is nitrogen, and the nitrogen flow rate is 1L / min;

[0094] S4, mixing resin hard carbon and petroleum asphalt in a mass ratio of 100:10 to obtain a mixture, wherein the softening point of the petroleum asphalt is 250° C. and the particle size Dv50 of the petroleum asphalt is 10 μm;

[0095] S5. Place the mixture in a CVD furnace, heat it to 400°C at a heating rate of 8°C / min under a nitrogen atmosphere, keep it warm for 1 hour, then switch the nitrogen to compressed air, and continue to keep it warm for 5 hours to obtain oxidative cross-linked asphalt-coated resin hard carbon; wherein the nitrogen flow rate is 1L / min, and the compressed air flow rate is 5L / min;

[0096] S6, placing the crucible containing the oxidized cross-linked asphalt coated resin hard carbon in a heating furnace and carbonizing it at 1300°C for 4 hours, cooling it to room temperature and taking it out to obtain coated hard carbon; wherein the atmosphere in the heating furnace is nitrogen, and the nitrogen flow rate is 1L / min;

[0097] S7. The coated hard carbon is sequentially broken up and depolymerized, sieved with a 325-mesh sieve, and demagnetized to obtain an oxidized cross-linked asphalt-coated resin hard carbon negative electrode material.

[0098] Comparative Example 3

[0099] This comparative example provides a method for preparing a resin hard carbon negative electrode material, the steps comprising:

[0100] S1, 20kg of phenolic resin and 10kg of anhydrous ethanol were mixed, stirred at room temperature for 1h, and then heated and cured in an oven at 95°C for 10h to obtain a resin precursor;

[0101] S2, the resin precursor is mechanically crushed and passed through a 12 mm mesh sieve, then placed in a heating furnace and kept at 400°C for 6 hours, cooled to room temperature, taken out and subjected to air flow crushing, and then sieved through a 325 mesh sieve to obtain a low-temperature pre-carbonized ground powder with a particle size Dv50 of 5 μm; wherein the atmosphere in the heating furnace is nitrogen, and the nitrogen flow rate is 1 L / min;

[0102] S3. Place the low-temperature pre-carbonized ground powder in a CVD furnace and activate and pore-form the powder at 800°C for 2 hours, then place it in a box-type furnace and carbonize it at 1300°C for 4 hours, then cool it to room temperature to obtain a resin hard carbon negative electrode material; wherein the atmosphere in the CVD furnace is a mixed gas of nitrogen and carbon dioxide, with a nitrogen flow rate of 1 L / min and a carbon dioxide flow rate of 2 L / min; the atmosphere in the box-type furnace is nitrogen, with a nitrogen flow rate of 1 L / min.

[0103] Comparative Example 4

[0104] This comparative example provides a method for preparing a resin hard carbon negative electrode material, the steps comprising:

[0105] S1, 20kg of phenolic resin and 10kg of anhydrous ethanol were mixed, stirred at room temperature for 1h, and then heated and cured in an oven at 95°C for 10h to obtain a resin precursor;

[0106] S2, the resin precursor is mechanically crushed and passed through a 12 mm mesh sieve, then placed in a heating furnace and kept at 400°C for 6 hours, cooled to room temperature, taken out and subjected to air flow crushing, and then sieved through a 325 mesh sieve to obtain a low-temperature pre-carbonized ground powder with a particle size Dv50 of 5 μm; wherein the atmosphere in the heating furnace is nitrogen, and the nitrogen flow rate is 1 L / min;

[0107] S3, placing the low-temperature pre-carbonized ground powder in a CVD furnace and activating and pore-forming treatment at 800°C for 2 hours, then placing it in a box furnace and high-temperature carbonizing at 1300°C for 4 hours and then cooling it to room temperature to obtain resin hard carbon; wherein the atmosphere in the CVD furnace is a mixed gas composed of nitrogen and carbon dioxide, the nitrogen flow rate is 1L / min, and the carbon dioxide flow rate is 2L / min; the atmosphere in the box furnace is nitrogen, and the nitrogen flow rate is 1L / min;

[0108] S4, placing the resin hard carbon in a CVD furnace, heating it to 350°C at a heating rate of 8°C / min under a nitrogen atmosphere, keeping it warm for 0.5h, then switching the nitrogen to compressed air, and keeping it warm for 3h to obtain oxidative cross-linked coated resin hard carbon; wherein the nitrogen flow rate is 1L / min, and the compressed air flow rate is 3L / min;

[0109] S5, placing the crucible containing the oxidative cross-linked coated resin hard carbon in a heating furnace and carbonizing it at 1250° C. for 4 hours, cooling it to room temperature and taking it out to obtain coated hard carbon; wherein the atmosphere in the heating furnace is nitrogen, and the nitrogen flow rate is 1 L / min;

[0110] S6. The coated hard carbon is sequentially broken up and deagglomerated, sieved with a 325-mesh sieve, and demagnetized to obtain a resin hard carbon negative electrode material.

[0111] Comparative Example 5

[0112] This comparative example provides a method for preparing a pitch-coated resin hard carbon negative electrode material, the steps comprising:

[0113] S1, 20kg of phenolic resin and 10kg of anhydrous ethanol were mixed, stirred at room temperature for 1h, and then heated and cured in an oven at 95°C for 10h to obtain a resin precursor;

[0114] S2, the resin precursor is mechanically crushed and passed through a 12 mm mesh sieve, then placed in a heating furnace and kept at 400°C for 6 hours, cooled to room temperature, taken out and subjected to air flow crushing, and then sieved through a 325 mesh sieve to obtain a low-temperature pre-carbonized ground powder with a particle size Dv50 of 5 μm; wherein the atmosphere in the heating furnace is nitrogen, and the nitrogen flow rate is 1 L / min;

[0115] S3, placing the low-temperature pre-carbonized ground powder in a CVD furnace and activating and pore-forming treatment at 800°C for 2 hours, then placing it in a box furnace and high-temperature carbonizing at 1300°C for 4 hours and then cooling it to room temperature to obtain resin hard carbon; wherein the atmosphere in the CVD furnace is a mixed gas composed of nitrogen and carbon dioxide, the nitrogen flow rate is 1L / min, and the carbon dioxide flow rate is 2L / min; the atmosphere in the box furnace is nitrogen, and the nitrogen flow rate is 1L / min;

[0116] S4, mixing resin hard carbon and petroleum asphalt in a mass ratio of 100:2 to obtain a mixture, wherein the softening point of the petroleum asphalt is 210° C. and the particle size Dv50 of the petroleum asphalt is 10 μm;

[0117] S5, placing the mixture in a crucible in a heating furnace and carbonizing it at 1250° C. for 4 hours, cooling it to room temperature and taking it out to obtain coated hard carbon; wherein the atmosphere in the heating furnace is nitrogen, and the nitrogen flow rate is 1 L / min;

[0118] S6. The coated hard carbon is sequentially broken up and deagglomerated, sieved with a 325-mesh sieve, and demagnetized to obtain a pitch-coated resin hard carbon negative electrode material.

[0119] Comparative Example 6

[0120] This comparative example provides a method for preparing an oxidatively cross-linked asphalt-coated resin hard carbon negative electrode material, the steps comprising:

[0121] S1, 20kg of phenolic resin and 10kg of anhydrous ethanol were mixed, stirred at room temperature for 1h, and then heated and cured in an oven at 95°C for 10h to obtain a resin precursor;

[0122] S2, the resin precursor is mechanically crushed and passed through a 12 mm mesh sieve, then placed in a heating furnace and kept at 400°C for 6 hours, cooled to room temperature, taken out and subjected to air flow crushing, and then sieved through a 325 mesh sieve to obtain a low-temperature pre-carbonized ground powder with a particle size Dv50 of 5 μm; wherein the atmosphere in the heating furnace is nitrogen, and the nitrogen flow rate is 1 L / min;

[0123] S3, mixing the low-temperature pre-carbonized ground material and petroleum asphalt in a mass ratio of 100:2 to obtain a mixture, wherein the softening point of the petroleum asphalt is 210° C. and the particle size Dv50 of the petroleum asphalt is 10 μm;

[0124] S4, placing the mixture in a CVD furnace, heating it to 350°C at a heating rate of 8°C / min under a nitrogen atmosphere, keeping it warm for 0.5h, then switching the nitrogen to compressed air, and continuing to keep it warm for 3h to obtain oxidative cross-linked asphalt-coated resin hard carbon; wherein the nitrogen flow rate is 1L / min, and the compressed air flow rate is 3L / min;

[0125] S5, placing the crucible containing the oxidized cross-linked asphalt coated resin hard carbon in a heating furnace and carbonizing it at 1250° C. for 4 hours, cooling it to room temperature and taking it out to obtain coated hard carbon; wherein the atmosphere in the heating furnace is nitrogen, and the nitrogen flow rate is 1 L / min;

[0126] S6. The coated hard carbon is sequentially broken up and depolymerized, sieved with a 325-mesh sieve, and demagnetized to obtain an oxidized cross-linked asphalt-coated resin hard carbon negative electrode material.

[0127] The particle size of the hard carbon negative electrode materials prepared in Examples 1 to 5 and Comparative Examples 1 to 6 was tested using a Malvern laser particle size analyzer MS2000; the specific surface area of ​​the hard carbon negative electrode materials prepared in Examples 1 to 5 and Comparative Examples 1 to 6 was tested using an American Quantachrome NOVA2000e instrument. The test results are shown in Table 1.

[0128] The hard carbon negative electrode materials of Examples 1 to 5 and Comparative Examples 1 to 6 were applied to half-cells according to the following method: the hard carbon negative electrode material was mixed with polyvinylidene fluoride and conductive carbon black in a mass ratio of 90:5:5, and applied to copper foil. The coated electrode was placed in a vacuum drying oven at a temperature of 110°C and vacuum dried for 4 hours for standby use, and then punched into a small disc with a diameter of 14 cm. Then it was transferred to a German Mikaelona glove box filled with argon gas and assembled into a 2430-type button cell, with a three-component mixed solvent of 1 mol / L NaClO4 in a mixed solution of EC:DMC:EMC=1:1:1 (volume ratio) as the electrolyte, a metal sodium sheet as the counter electrode, and a 16 μm thick Ube diaphragm as the isolation membrane to form a half-cell. The electrochemical performance of the assembled half-cell was tested on the Arbin electrochemical detection system in the United States, with a charge and discharge voltage range of 0V to 2.0V, a rate of 0.1C, and the first reversible capacity and the first charging efficiency were recorded. The results are shown in Table 1.

[0129] Table 1

[0130]

[0131] By comparing Example 5 with Comparative Examples 1 to 2, it can be seen that when the mass ratio of resin hard carbon to asphalt is not in the range of 100:1 to 5, the prepared hard carbon negative electrode material cannot significantly improve the first reversible capacity and initial coulombic efficiency of the battery. This shows that the mixing ratio of resin hard carbon and asphalt has an important influence on the microstructure of the final hard carbon negative electrode material. If the ratio is not appropriate, it may lead to unreasonable internal pore distribution of the generated hard carbon negative electrode material, insufficient or excessive graphitization, etc., thereby affecting its electrochemical performance as a negative electrode material for lithium-ion batteries.

[0132] By comparing Example 5 with Comparative Examples 4 to 5, it can be seen that uniformly mixing the resin hard carbon and asphalt and subjecting them to low-temperature oxidation treatment can make the coated hard carbon have higher mechanical strength, more closed pores and ultrafine pores, reduce the specific surface area of ​​the resin hard carbon, improve the surface wettability of the resin hard carbon and the electrolyte, facilitate the diffusion and adsorption of sodium ions, and significantly improve the first reversible capacity and initial coulombic efficiency of the battery.

[0133] By comparing Example 5 and Comparative Example 6, it can be seen that if the activation pore-forming treatment and the first high-temperature carbonization treatment process in S3 are removed, the uniform coating of asphalt and resin hard carbon will be affected, and thus uniformly distributed closed pores and ultrafine pores cannot be formed in subsequent steps, and the first reversible capacity and initial coulombic efficiency of the battery cannot be significantly improved.

[0134] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing an oxidatively cross-linked asphalt-coated resin hard carbon negative electrode material, characterized in that the steps include: S1, pre-treating the resin to obtain a resin precursor; S2, sequentially subjecting the resin precursor to mechanical pulverization, low-temperature pre-carbonization under a first inert atmosphere, and airflow pulverization to obtain a low-temperature pre-carbonized abrasive material; S3, subjecting the low-temperature pre-carbonized ground powder to activation pore-forming treatment and first high-temperature carbonization treatment in sequence to obtain resin hard carbon; S4, mixing the resin hard carbon and asphalt uniformly to obtain a mixture, wherein the mass ratio of the resin hard carbon to the asphalt is 100:1-5; S5, melting and coating the mixture with asphalt in a protective atmosphere, and then switching the protective atmosphere to air atmosphere for low-temperature oxidation cross-linking treatment to obtain oxidative cross-linked asphalt-coated resin hard carbon; S6, subjecting the oxidatively cross-linked asphalt-coated resin hard carbon to a second high-temperature carbonization treatment in a second inert atmosphere to obtain coated hard carbon; S7, post-processing the coated hard carbon to obtain coated hard carbon powder.

2. The method for preparing the oxidatively cross-linked asphalt-coated resin hard carbon negative electrode material according to claim 1, characterized in that: The pretreatment in step S1 includes: mixing the resin and the solvent, then performing homogenization and heating and curing in sequence.

3. The method for preparing the oxidatively cross-linked asphalt-coated resin hard carbon negative electrode material according to claim 2, characterized in that: The temperature of the heating curing in step S1 is 60° C. to 200° C., and the time is 5 h to 50 h.

4. The method for preparing the oxidatively cross-linked asphalt-coated resin hard carbon negative electrode material according to claim 2, characterized in that: The resin is at least one of phenolic resin, epoxy resin and furfural resin; the solvent is at least one of water, alcohol and ketones.

5. The method for preparing an oxidatively cross-linked asphalt-coated resin hard carbon negative electrode material according to claim 1, characterized in that: The temperature of the low-temperature pre-carbonization in step S2 is 350° C. to 700° C., and the time is 0.5 h to 10 h.

6. The method for preparing the oxidatively cross-linked asphalt-coated resin hard carbon negative electrode material according to claim 1, characterized in that: The atmosphere of the activation pore-forming treatment in step S3 is a mixed gas composed of at least two of water vapor, carbon dioxide and nitrogen. The temperature of the activation pore-forming treatment is 700° C. to 1000° C., and the time is 1 h to 10 h.

7. The method for preparing an oxidatively cross-linked asphalt-coated resin hard carbon negative electrode material according to claim 1, characterized in that: In step S3, the temperature of the first high-temperature carbonization treatment is 1100° C. to 1600° C., and the time is 0.5 h to 8 h.

8. The method for preparing an oxidatively cross-linked asphalt-coated resin hard carbon negative electrode material according to claim 1, characterized in that: The asphalt in step S4 is selected from coal asphalt and petroleum asphalt, and the softening point of the asphalt is 100-280°C.

9. The method for preparing an oxidatively cross-linked asphalt-coated resin hard carbon negative electrode material according to claim 1, characterized in that: The invention comprises at least one of the following features (1) to (8): (1) In step S2, the first inert atmosphere is at least one of argon and nitrogen; (2) The particle size Dv50 of the low-temperature pre-carbonized ground powder in step S2 is 4 μm to 10 μm; (3) The particle size Dv50 of the asphalt in step S4 is 2 μm to 5 μm; (4) The asphalt melt coating in step S5 includes: heating to 200-400°C at a heating rate of 1-10°C / min under a protective atmosphere, and keeping the temperature for 0.5-5h; the low-temperature oxidation cross-linking treatment includes: keeping the temperature at 200-400°C for 0.5-5h; (5) The protective atmosphere in step S5 is at least one of argon and nitrogen; (6) The low-temperature oxidation cross-linking treatment in step S5 is carried out in a box furnace, a CVD furnace, a rotary kiln, a pusher kiln, a roller kiln or a tunnel kiln; (7) In step S6, the second inert atmosphere is at least one of argon and nitrogen, the temperature of the second high-temperature carbonization treatment is 1100° C. to 1600° C., and the time is 0.5 h to 8 h; (8) The post-treatment in step S7 includes depolymerization, screening, and demagnetization treatment in sequence.

10. An oxidatively cross-linked asphalt-coated resin hard carbon negative electrode material, characterized in that: The material is prepared by the method for preparing an oxidatively cross-linked asphalt-coated resin hard carbon negative electrode material as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Composite hard carbon negative electrode material, and preparation method and application thereof

    CN103311519A

  • Preparation method of high capacity lithium ion battery hard carbon composite negative electrode material

    CN106532009A

  • Preparation method and modification method of hard carbon negative electrode material for lithium ion power batteries

    CN106981629A

  • Sodium-ion battery hard carbon negative electrode material with high compaction density and low specific surface area and preparation method of sodium-ion battery hard carbon negative electrode material

    CN117361496A

Cited By

  • A hard carbon negative electrode material and preparation method thereof and sodium ion battery

    CN119750549A

  • Controllable construction method for carbon layer structure on hard carbon surface and application of controllable construction method

    CN120463182A